2002
DOI: 10.1038/sj.bjc.6600023
|View full text |Cite
|
Sign up to set email alerts
|

Occupational physical activity and risk for prostate cancer in a nationwide cohort study in Sweden

Abstract: We investigated effects of occupational physical activity on relative risk for prostate cancer. From Swedish nationwide censuses in 1960 and 1970, we defined two cohorts of men whose occupational titles allowed classification of physical activity levels at work in 1960 (n=1 348 971) and in 1970 (n=1 377 629). A third cohort included only men whose jobs required a similar level of physical activity in both 1960 and 1970 (n=673 443). The incidence of prostate cancer between 1971 and 1989 was ascertained through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 37 publications
3
30
0
2
Order By: Relevance
“…Our result of no overall inverse association between occupational activity and prostate cancer is consistent with most, 12,16,[19][20][21][22][23][24][25] but not all, [5][6][7]13 previous studies. That physical activity is more strongly, inversely related to risk of advanced, high-grade or aggressive prostate cancer has, however, been indicated previously.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our result of no overall inverse association between occupational activity and prostate cancer is consistent with most, 12,16,[19][20][21][22][23][24][25] but not all, [5][6][7]13 previous studies. That physical activity is more strongly, inversely related to risk of advanced, high-grade or aggressive prostate cancer has, however, been indicated previously.…”
Section: Discussionsupporting
confidence: 79%
“…' 2009 UICC cancer is inconsistent, and in a new report from World Cancer Research Fund and American Institute for Cancer Research the expert panel concludes that the evidence for an association between physical activity and prostate cancer is too limited for a formal judgment. 3 Of the 22 published cohort studies, 9 found an inverse association of prostate cancer risk with cardiorespiratory fitness, 4 occupational activity, 5,6 leisure time activity [7][8][9][10][11] or both leisure time activity and occupational activity. 12 One study found an increased risk of prostate cancer among college athletes 13 and 12 studies found no significant association.…”
mentioning
confidence: 99%
“…often represent a great range of possible chemicals and exposure levels. Industry-based studies that can access employment records and other data sources for exposure assessment and allow the creation of a job exposure matrix (JEM) usually improve exposure assessment [Goldberg et al, 1993]; but such studies often do not have access to or are unable to collect information on potential non-occupational confounding risk factors [Dosemeci et al, 1993;Hsing et al, 1994;Krstev et al, 1998;Buxton et al, 1999;Brown and Delzell, 2000;Norman et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…In a longitudinal study conducted by the Veteruntreated hypertension among adults and His-390 350 ans Administration at the Boston Outpatient Clinic panics is the isolated systolic hypertension 391 351 Lee et al found that in the elderly mate, pulse [6,31,[36][37][38]. 392 352 pressure, may be a more accurate predictor of An analogous strategy used in nutritional epide-393 353 cardiovascular death than either systolic blood miology to study highly correlated variables such as 394 354 pressure or diastolic blood pressure alone [27].…”
Section: Discussionmentioning
confidence: 99%